Analisis Metode Mengajar Guru Dalam Meningkatkan Minat Belajar Siswa - Diana Martiani Situmeang; Anggita Manda Manik; Ganti Meriah Manik; Agnes Dewi Rohani Siahaan; Freddi Saragi; Riswan E. A Manik (Journal on Education, 2024)
This research was conducted to determine the learning methods used by teachers to increase interest in learning. This study uses a qualitative method. The findings of this research are the learning methods used by teachers to increase students' varied interest in learning. Variations in methods include lecture, discussion, question and answer, assignment, demonstration, example, advice, reward and punishment, and learning outside the classroom. It is hoped that this varied learning method can increase students' interest in learning.